24. CAUSES AND TREATMENT RESULTS OF COMMUNITY-ACCURED PNEUMONIA IN CHILDREN FROM 1 MONTH TO 5 YEARS OLD AT THE RESPIRATORY DEPARTMENT OF NGHE AN OBSTETRICS AND PEDIATRIC HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Purpose: Identifying the bacterial causes of community-acquired pneumonia and commenting on the treatment results of some common bacteria in children from 1 month to 5 years old at the Respiratory Department, Nghe An Obstetrics and Pediatrics Hospital.Methods: Descriptive cross-sectional study.Results: The age group of 1-12 months accounted for 48.8%, the male/female ratio was 1.48/1. The main clinical symptoms were cough (100%), wheezing (74.3%), rapid breathing (98.8%), and rales in the lungs (100%). Leukocytosis (74.5%), increased CRP (58.6%). Lesions on the chest X-ray showed opacity of the hilum next to the heart in 50.6%, diffuse opacity in 46.9%, and interstitial lung lesions in 10.3%. Culture of the nasopharyngeal fluid: H.influenzae accounted for 50.6%, followed by S. pneumoniae 38.4%, M.catarrhalis (9.8%), P.aeruginosa (0.6%), and E.coli (0.6%). The initial antibiotic treatment was single-use Cefalosporin (70.7%). 17.6% of children had to change the type of antibiotic used initially. Average treatment time: 8.067 +- 2.837 days. The rate of disease improvement was 65.2%, cure rate was 33.5%, no children had to be transferred to a higher level or died in both the S.pneumoniae and H.influenzae pneumonia groups.Conclusion: The age group of 1-12 months accounted for the majority of 48.8%, the male/female ratio was 1.48/1. The main clinical symptoms: cough, wheezing, rapid breathing, rales in the lungs. Increased white blood cells (74.5%), increased CRP (58.6%). Lesions on chest X-ray: blurred hilum next to the heart accounted for 50.6%. Culture of nasopharyngeal secretions: H.influenzae accounted for the majority of 50.6%. Average treatment time: 8.067 +- 2.837 days.
Keywords: Community Acquired Pneumonia; Streptococcus pneumonia; antibiotic resistance